ANALISIS KARAKTERISTIK PARKIR BADAN JALAN DI KAWASAN PERTOKOAN MEGAHRIA KOTA PALEMBANG - Hariman Al Faritzie; Felly Misdalena; Wartini (LATERAL: Jurnal Teknik Sipil, 2023)
The megahria shopping area Jl.T.P.Rustam Effendi is located in the Ilir Timur 1 sub-district Palembang city. With the increasing number of residents which continues to increase from time to time, the need for transfortation mobility is getting bigger. This also has an impact on the available parking lots in the megahria shopping area of Palembang city. Facts in the field show that on of the problems of the transportation system in the availability of inadequate parking space, so this research was conducted to analyze the characteristics of the magnitude of the impact caused by the operation of roadside parking in the megahria shopping area of palembang city with the research object being motorcycles and passenger cars who only use parking facilities inside the road body parking lot in the megahria shopping area of Palembang city. Based on parking characteristics it can be concluded that the conditions and needs of on-street parking spaces in the megahria shopping area of Palembang city. From the calculation for passenger car vehicles in can be 436 vehicles, the Parking space requirement is 209 parking spaces. While the total for motorcycle vehicles is 2173 vehicles, the current parking spaces requirement is 766 parking spaces.